Temporary Food Plot Deterrents for Deer: Do They Work? - Holly Ober; Cheryl Mackowiak; Ann Blount (EDIS, 2016)
Many Floridians enjoy the opportunity to hunt, watch, or photograph white-tailed deer. Hunters and landowners often plant cool season forage plots both to attract wildlife and to provide a dependable food source. But where there is a high deer population or scarce food resources, deer may forage on food plots as soon as the plants emerge and before they become established. This 5-page fact sheet presents the results of research conducted at the UF/IFAS North Florida Research and Education Center in Quincy into the effectiveness of various strategies hunters and landowners can use to temporarily limit access to new food plots until the plants are well established and strong enough to attract and sustain hungry deer through the winter. Written by Holly Ober, Cheryl Mackowiak, and Ann Blount, and published by the UF/IFAS Department of Wildlife Ecology and Conservation, February 2016.